1996
DOI: 10.1063/1.471007
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond study of Xe-Cl2 reactions in clusters

Abstract: The reaction of a xenon atom with a chlorine molecule has been studied in the femtosecond regime using the pump (395 nm) and probe (308 nm) technique in Xe-Cl2 clusters. The electronically excited reaction product XeCl was observed both after a simultaneous and a sequential (with a delay of ≊500 fs) absorption of the pump and probe photons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…7͒ and, more recently, XeϩCl 2 . 8 The specific system of interest here is the bimolecular reaction of polyatomic molecules ͑electron donor, D͒ benzene ͑Bz͒, or methyl substituted benzenes ͑MBz͒ with a diatomic molecule ͑electron acceptor, A͒ of molecular iodine ͑I 2 ͒; see Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…7͒ and, more recently, XeϩCl 2 . 8 The specific system of interest here is the bimolecular reaction of polyatomic molecules ͑electron donor, D͒ benzene ͑Bz͒, or methyl substituted benzenes ͑MBz͒ with a diatomic molecule ͑electron acceptor, A͒ of molecular iodine ͑I 2 ͒; see Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…8 If the lifetime of this intermediate complex is short, however, the initial conditions still determine the reaction outcome. 31 Recent two-photon femtosecond studies 17,32 suggest that this is in fact the case in the reaction originating from collision pairs in low pressure gas mixtures. In the latter study, 32 Dedonder-Lardeux et al also identified a second entrance channel occurring some 500 fs after the initial photon absorption in the reaction originating from vdW complexes.…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent two-photon femtosecond studies 17,32 suggest that this is in fact the case in the reaction originating from collision pairs in low pressure gas mixtures. In the latter study, 32 Dedonder-Lardeux et al also identified a second entrance channel occurring some 500 fs after the initial photon absorption in the reaction originating from vdW complexes. This delayed entrance channel is also transient, and therefore is thought to occur within Xe n Cl 2 clusters where cage effects allow a recoil of the dissociating Cl atom.…”
Section: Discussionmentioning
confidence: 99%
“…Laser induced harpoon reactions, the most common of which are those between rare gas atoms ͑Rg͒ and molecular halogens ͑X 2 ͒ or halogen containing polyatomic molecules ͑RX͒, have been extensively studied in the gas phase, [1][2][3][4][5][6][7][8] in clusters produced in molecular beams, [9][10][11] in the solid state, [12][13][14][15][16] and in the liquid phase. 13,14,[17][18][19] This class of photochemical reactions is useful in studies of fundamental chemical dynamics, and in particular, bimolecular chemistry, in condensed media.…”
Section: Introductionmentioning
confidence: 99%
“…19 This observation has been more recently verified by time resolved measurements in clusters containing Cl 2 and Xe. 10 In the latter two color experiments, with a probe wavelength of 308 nm, a delayed transient signal due to the sequential process of Eq. ͑5͒ could also be seen.…”
Section: Introductionmentioning
confidence: 99%